Statistical optimization of dilute acid pretreatment of lignocellulosic biomass by response surface methodology to obtain fermentable sugars for bioethanol production - Yildirim, Oznur; Ozkaya, Bestami; Altinbas, Mahmut; Demir, Ahmet (WILEY, 2021)
Central composite design to optimize sugar recovery from cotton straw and sunflower straw using dilute acid pretreatment was applied. Selected input variables were acid concentration, retention time, and temperature, as well as the response parameter of sugar yield. The optimum pretreatment conditions observed for maximum sugar yield are temperature: 121.7 degrees C, acid concentration: 2.28% (vol/vol), and time: 36.82 minutes for cotton straw; temperature: 87.03 degrees C, and acid concentration: 3.68% (vol/vol), and time: 36.82 minutes for sunflower straw. Maximum sugar concentrations were corresponded to 20 and 17.5 g L-1 under conditions for sunflower and cotton straw, respectively. This study not only investigates the sugar recovery efficiency statistically but also examines the ethanol production efficiency. As a result, the maximum ethanol concentration, ethanol yield, and ethanol productivity of 7.21 g L-1, 0.41 g g(-1), and 0.10 g L-1 h(-1) for cotton straw and 8.05 g L-1, 0.40 g g(-1), and 0.11 g L-1 h(-1) for sunflower straw were achieved via fermentation with Saccharomyces cerevisiae, respectively. The output of this study is important for the commercialization of bioprocesses that enable the conversion of the lignocellulosic waste matrix into high value-added products in a biorefinery concept.
Keywords: bioethanol; fermentation; lignocellulose; pretreatment; response surface methodology; sugar recovery; ETHANOL FERMENTATION; HYDROGEN-PRODUCTION; COTTON STALK; SACCHAROMYCES-CEREVISIAE; ENZYMATIC-HYDROLYSIS; ZYMOMONAS-MOBILIS; TEMPERATURE; KINETICS; BIOCONVERSION; PH; Energy & Fuels; Nuclear Science & Technology